The Evolving Modern Management of Brain Metastasis - Peter E. Fecci; Cosette D. Champion; Jacob P. Hoj; Courtney McKernan; C. Rory Goodwin; John P. Kirkpatrick; Carey K. Anders; Ann Marie Pendergast; John H. Sampson (2019)
The incidence of brain metastases is increasing as cancer therapies improve and patients live longer, providing new challenges to the multidisciplinary teams that care for these patients. Brain metastatic cancer cells possess unique characteristics that allow them to penetrate the blood-brain barrier, colonize the brain parenchyma, and persist in the intracranial environment. In addition, brain metastases subvert the innate and adaptive immune system, permitting evasion of the antitumor immune response. Better understanding of the above mechanisms will allow for development and delivery of more effective therapies for brain metastases. In this review, we outline the molecular mechanisms underlying development, survival, and immunosuppression of brain metastases. We also discuss current and emerging treatment strategies, including surgery, radiation, disease-specific and mutation-targeted systemic therapy, and immunotherapy.